2016
DOI: 10.1007/s40258-016-0243-4
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Bendamustine Plus Rituximab as a First-Line Treatment for Patients with Follicular Lymphoma in Spain

Abstract: First-line therapy with rituximab-bendamustine in FL patients was the dominant strategy over treatment with R-CHOP; it showed cost savings and higher health benefits for the Spanish NHS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Six studies were found to report cost effectiveness of treatments for relapsed/refractory (R/R) FL, while only three studies reported cost-effectiveness evidence for refractory FL. A Markov modelling approach, mainly depicting a three-state disease model (progression-free, progressive disease and death), was used in the majority of costeffectiveness publications [8,11,18,[20][21][22][23][24][25]. Other analysis types used included cohort-based analysis [26], probabilistic decision analytic model [9], transitional state model [19], and a partitioned survival model [27].…”
Section: Model/analysis Design Overviewmentioning
confidence: 99%
“…Six studies were found to report cost effectiveness of treatments for relapsed/refractory (R/R) FL, while only three studies reported cost-effectiveness evidence for refractory FL. A Markov modelling approach, mainly depicting a three-state disease model (progression-free, progressive disease and death), was used in the majority of costeffectiveness publications [8,11,18,[20][21][22][23][24][25]. Other analysis types used included cohort-based analysis [26], probabilistic decision analytic model [9], transitional state model [19], and a partitioned survival model [27].…”
Section: Model/analysis Design Overviewmentioning
confidence: 99%
“…Studies recruiting an EU population accounted for the greatest proportion of research (41%) ( Figure 2D). (16 studies [24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39])…”
Section: Study Characteristicsmentioning
confidence: 99%
“…CIA management costs associated with CHOP or some variation have been included in several economic modelling studies but they focus on inpatient costs only, and are largely not contemporary estimates (pre-2014) [26,34,36]. One Dutch study reported other medical resource use associated with CIA limited to moderate costs associated with transfusion (costs of RBCs transfused EUR 398 to EUR 553 (cost year not stated) [44]).…”
Section: Summary Findings: Febrile Neutropeniamentioning
confidence: 99%
See 2 more Smart Citations